Pengurusan Sign On/Off Buku Pelaut Crew Kapal pada KSOP Kelas I Panjang oleh PT. Baruna Mitra Segara Lines Bandar Lampung - Pebriyanti Pebriyanti; Dirhamsyah Dirhamsyah; Eka Fransiska (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The process of signing on and off a seafarer's book for ship crew is a vital stage in the shipping world that requires thorough preparation and orderly implementation to ensure the safety and smooth operation of the ship. Signing on a seafarer's book involves recording and confirming the date and location of boarding the ship in the seafarer's book, which serves as official proof that the document holder has joined the ship's crew. Generally, this stage is accompanied by the preparation of a Seafarer's Employment Agreement (PKL) containing salary details and obtaining approval from the Harbor Master. Conversely, sign off is a procedure carried out when the work contract period in the PKL ends, or earlier for certain reasons such as late salary payments or discomfort in the work. The purpose of this study is to identify the obstacles that arise in the process of managing the sign-on/off of seafarer's crew books at PT. Baruna Mitra Segara Lines, Bandar Lampung. In compiling this paper, the author applies two approaches, namely the field observation method (field study) and the library study method. Both methods are used to gain a comprehensive understanding of the mechanism for managing the sign-on/off of seafarer's books, while also identifying the obstacles that arise so that the company can maximize the process. The research findings reveal that there are obstacles in the implementation of the sign-on/off of seafarer's books that are not fully in accordance with procedures. However, this process still has a positive and significant impact on the efficiency of the departure time of ship crews. This finding confirms that improving procedures and enforcing operational standards are key to improving the quality of document management services at PT. Baruna Mitra Segara Lines